Quintus Cicero and Roman Rule. Networks between Centre and Periphery - Vogel, Christian (Journal of Historical Network Research, 2020)
This chapter analyses the governorship of Quintus Tullius Cicero (102[?]-43 BCE) during his three year-long administration of the province of Asia from 61 to 58 BCE and during his command of a Roman legion under Caesar in Gaul in 54 BCE. Both commands represent different stages and situations of Roman rule over different regions and cultures. The relationship between rulers and ruled, between governors and governed peoples, will be studies by means of SNA. The chapter will examine Quintus’ networks in Gaul and in Asia and situate them within the larger sphere of Roman government. It will also discuss the benefits and obstacles that historical network research has to face in these examples and present considerations to provide grounds for more general reflections on the application of SNA in Greco-Roman history, especially regarding structures of control and empires.